Membrane potential-dependent uptake of cationic oligoimidazolium mediates bacterial DNA damage and death - Yong, Melvin (2023)
The treatment of bacterial infections is becoming increasingly challenging with the emergence of antimicrobial resistance. Thus, the development of antimicrobials with novel mechanisms of action is much needed. Previously, we designed several cationic main-chain imidazolium compounds and identified the polyimidazolium PIM1 as a potent antibacterial against a wide panel of multidrug-resistant nosocomial pathogens, and it had relatively low toxicity against mammalian epithelial cells. However, little is known about the mechanism of action of PIM1. Using an oligomeric version of PIM1 with precisely six repeating units (OIM1-6) to control for consistency, we showed that OIM1-6 relies on an intact membrane potential for entry into the bacterial cytoplasm, as resistant mutants to OIM1-6 have mutations in their electron transport chains. These mutants demonstrate reduced uptake of the compound, which can be circumvented through the addition of a sub-MIC dose of colistin. Once taken up intracellularly, OIM1-6 exerts double-stranded DNA breaks. Its potency and ability to kill represents a promising class of drugs that can be combined with membrane-penetrating drugs to potentiate activity and hedge against the rise of resistant mutants. In summary, we discovered that cationic antimicrobial OIM1-6 exhibits an antimicrobial property that is dissimilar to the conventional cationic antimicrobial compounds. Its killing mechanism does not involve membrane disruption but instead depends on the membrane potential for uptake into bacterial cells so that it can exert its antibacterial effect intracellularly.